Corporate Social Responsibility Disclosure and Firm Value: Does Firm Size Matter? - Lina, Lina; Ivada, Bernika Irnadia (Jurnal Akuntansi, 2025)
Purpose – The objective of this study is to investigate the positive effect of corporate social responsibility disclosure on firm value. It also aims to empirically demonstrate the role of firm size as a moderator on the relationship between corporate social responsibility disclosure and firm value. Design/Methodology/Approach – This research employs a quantitative approach and utilizes secondary data. The selected sample comprised 29 energy sector companies listed on the main board of the Indonesia Stock Exchange for the 2018-2022 period. Hypothesis testing used multiple and moderated linear regression. Findings – The findings of this study successfully confirmed all existing hypotheses. Corporate social responsibility disclosure has a positive effect on firm value. Firm size has been shown to moderate this positive effect. Research limitations/Implications – This research limits its sample to energy sector companies listed on the Indonesia Stock Exchange during the 2018-2022 period. This research did not consider the impact of the COVID-19 pandemic that occurred in 2020. Keywords: Corporate Social Responsibility, Firm Size, Firm Value, Indonesia